Dermatological manifestations in children and adults with COVID-19 infections - Abhilasha Williams; Amrutha Dirisala; Monika Sharma (Wolters Kluwer Medknow Publications, 2020)
The cutaneous manifestations of COVID-19 infection are evolving rapidly as new data continue to be published in the literature. Considering that majority of these manifestations resemble other viral exanthemas, a high degree of suspicion and clinical acumen is needed for early identification of COVID-19 infections and its prompt management. The most common manifestations in adults include maculopapular rash, purpura, vesicular rash, urticarial rash, and pseudo-chilblains, while in children, the manifestations include Kawasaki disease-like inflammatory syndrome (pediatric inflammatory multisystem syndrome) and erythema multiforme. This review presents a comprehensive guide to the cutaneous manifestations of COVID-19 infections in adults and children. Also included are the dermatological manifestations observed due to prolonged use of personal protective equipment in healthcare workers.